Electricity Theft as an Economic Crime: Legal and Policy Analysis in Indonesia - Martha Damita Palilu; Hendrik Salmon; Hadibah Wadjo (Ridwan Institute, 2026)
This study examines electricity theft as an economic crime within the Indonesian legal framework, focusing on its legal implications, enforcement challenges, and impact on state financial interests. The background of this research is rooted in the increasing occurrence of electricity theft, which not only causes financial losses to PT PLN (Persero) but may also contribute to broader state financial losses due to its status as a state-owned enterprise managing public assets. The objective of this study is to analyze the criminal liability of electricity theft offenders and to evaluate the effectiveness of legal enforcement under Law Number 30 of 2009 concerning Electricity. The method used is normative legal research with statutory, conceptual, and comparative approaches. Legal materials were collected through library research and analyzed qualitatively to examine relevant legal norms, doctrines, and judicial interpretations. The results show that electricity theft is explicitly regulated as a criminal offense and should be treated as an economic crime affecting the public interest. However, enforcement practices in Indonesia tend to rely more on administrative sanctions through the Electricity Usage Control Program (P2TL), which reduces the deterrent effect of criminal law. The study concludes that stronger criminal enforcement, clearer legal interpretation of state financial loss, and the integration of modern monitoring technologies are necessary to improve electricity theft prevention and strengthen energy governance in Indonesia.